THE IMPACT OF MONETARY SHOCKS ON ECONOMIC VOLATILITY IN IRAQ DURING THE PERIOD 2004-2023 (World Economics and Finance Bulletin, 2025)
The paper examines the issue of monetary shocks and likely impacts on economic volatility in Iraq between the years 2004 and 2023. It demonstrates that the variation in the supply of money, inflation, and exchange rates has a huge impact on GDP, investment, and expenditure. Based on the SVAR model, the study discovers that the growth policies, which includes injecting more money into the economy, have a positive effect in the short run, and the effects of inflation and currency fluctuation are negative. It also comes out in the results that government policy is constrained by structural factors such as overdependence on oil and poor harmonization between monetary and fiscal plans. The impulse response analysis proves that the exchange rate shocks have the highest long-term impact across all sectors. The study advises that two possible areas to focus on are stabilizing the inflation and the exchange rates and advancing the budget control and oil independence. It is also an indication of improved coordination among the institutions of the government to prevent further economic risks. With transparent fiscal roads and the prudent use of money, Iraq will be able to stabilize its economic growth since it will be better equipped to absorb any shocks that are thrown at it in the future.